Penilaian Autentik: Penerapan dan Dampak Kualitas Hasil Belajar Terhadap Mata Kuliah Bahasa Inggris - Helmy Sahirul Alim (Jurnal Bahasa Inggris Terapan, 2019)
This study aims to find out how the application of authentic methods and what their impact on the quality of student learning outcomes. This research method used descriptive qualitative where the data obtained is presented based on facts in the field. The subjects of this study were 3 lecturers and 32 first grade students who were taking Bahasa Inggris 2 (English 2) in Teknik Bangunan Kapal (Ship Building Engineering) in Politeknik Negeri Madura. 3 aspects of authentic assessment are the focus of this study to assess student learning processes. These three things are the assessment of student performance (performance), assessment of student attitudes (attitude), and product assessment (product). Based on the three aspects above, the researcher found that in its application this method was very suitable to be used in the Polytechnic environment considering that the learning patterns were very focused on real cases that occurred with all the solutions to the problems. As for the learning outcomes that have been found in this study are the activeness or the participation of students in using English in solving problems that have been predetermined by researchers. This is because in its application authentic assessment does not focus on traditional assessment such as examinations.